Expression of NGAL-specific cells and mRNA levels correlate with inflammation in the salivary gland, and its overexpression in the saliva, of patients with primary Sjögren’s syndrome - Lara A. Aqrawi; Janicke Liaaen Jensen; Siren Fromreide; Hilde Kanli Galtung; Kathrine Skarstein (Autoimmunity, 2020)
Salivary gland involvement is a characteristic feature of primary Sjögren’s syndrome (pSS), where tissue destruction is mediated by infiltrating immune cells, and may be accompanied by the presence of adipose tissue. Optimally diagnosing this multifactorial disease requires the incorporation of additional routines. Screening for disease-specific biomarkers in biological fluid could be a promising approach to increase diagnostic accuracy. We have previously investigated disease biomarkers in saliva and tear fluid of pSS patients, identifying Neutrophil gelatinase-associated lipocalin (NGAL) as the most upregulated protein in pSS. In the current study, we aimed to explore for the first time NGAL expression at the site of inflammation in the pSS disease target organ. Immunohistochemical staining was conducted on minor salivary gland biopsies from 11 pSS patients and 11 non-SS sicca subjects, targeting NGAL-specific cells. Additional NGAL/PNAd double staining was performed to study NGAL expression in high endothelial venules, known as specialised vascular structures. Moreover, NGAL mRNA expression was measured utilising quantitative real-time polymerase chain reaction (qRT-PCR) on minor salivary gland biopsies from 15 pSS patients and 7 non-SS sicca individuals that served as tissue controls. Our results demonstrated NGAL expression in acinar and ductal epithelium within the salivary gland of pSS patients, where significantly greater levels of acinar NGAL were observed in pSS patients (p < .0018) when compared to non-SS subjects. Also, acinar expression positively correlated with focus score values (r2 = 0.54, p < .02), while ductal epithelial expression showed a negative such correlation (r2 = 0.74, p < .003). Some PNAD+ endothelial venules also expressed NGAL. An increase in NGAL staining with increased fatty replacement was also observed in pSS patients. Concurringly, a 27% increase in NGAL mRNA levels were also detected in the minor salivary glands of pSS patients when compared to non-SS tissue control subjects. In conclusion, there is a positive association between increase in NGAL expression and inflammation in the pSS disease target organ, which also coincides with its previously demonstrated upregulation in the saliva of pSS patients. Additional functional analyses are needed to better understand the immunological implications of this potential biomarker.